Immunolocalisation of phosphorylated STAT3, interleukin 11 and leukaemia inhibitory factor in endometrium of women with unexplained infertility during the implantation window - Salamonsen Lois A; Tan Yee; Sharkey Andrew M; Dimitriadis Evdokia; Sherwin J Robert A (BMC, 2007)
Abstract Background Uterine receptivity and embryo implantation are critical in the establishment of pregnancy. The diagnosis of endometrial fertility requires more precise measurements of endometrial receptivity. Interleukin (IL-11) and leukemia inhibitory factor (LIF) are essential for murine implantation and signal via intracellular phosphorylation (p) of STAT3 in the endometrium. Both cytokines are present in the endometrium of women duiring the receptive window. Endometrial IL-11, IL-11 receptor alpha (IL-11Ralpha), LIF and pSTAT3 in women with primary unexplained infertility was compared to normal fertile women during the implantation window. Methods LH timed endometrial biopsies (LH+6 to LH+10) were collected from women with unexplained infertility and normal fertility. pSTAT3, IL-11, IL-11Ralpha and LIF production was determined by immunohistochemistry. Staining intensity was determoned by two independent observers blind to the fertility status of the patient from whom the biopsy was taken. Staining intensity and heterogeneity in each of the endometrial compartments (epithelium; stroma, including decidualized stromal cells; and vasculature) was assessed. The Mann-Whitney U test was used to analyze IL-11, pSTAT3, IL-11Ralpha and LIF immunostaining intensities in the samples. Results IL-11, IL-11Ralpha and LIF were present predominantly in glandular epithelium, whilst luminal epithelium showed patchy staining. pSTAT3 was present in both glandular epithelium and stroma. IL-11 and pSTAT3 immunostaining was significantly lower in glandular epithelium in infertile women compared to controls (P < 0.05) whilst IL-11Ralpha and LIF staining did not differ. Conclusion This is the first demonstration of reduced endometrial pSTAT3 and IL-11 in some women with unexplained infertility. This suggests IL-11 and pSTAT3 may be involved in the secretory transformation of glandular epithelium during receptivity. Reduced IL-11 production and STAT3 phosphorylation may contribute to unexplained infertility in some women.